2010
DOI: 10.1186/1471-2474-11-156
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1, placebo-controlled, dose escalation trial of chicory root extract in patients with osteoarthritis of the hip or knee

Abstract: BackgroundExtracts of chicory root have anti-inflammatory properties in vitro and in animal models of arthritis. The primary objective of this investigator-initiated, Phase 1, placebo-controlled, double blind, dose-escalating trial was to determine the safety and tolerability of a proprietary bioactive extract of chicory root in patients with osteoarthritis (OA). Secondary objectives were to assess effects on the signs and symptoms of this disorder.MethodsIndividuals greater than 50 years of age with OA of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Of the studies in our survey, four studies were performed without running a placebo group [12,14,16,17] and five trials did not include an active comparator [15,[18][19][20][21], clearly limiting the informative value of the studies. The particular importance of control groups for trials on OA has been underscored by a systematic review and meta-analysis involving 193 placebo (16,364 patients) and 14 untreated control groups (1167 patients) from RCTs, showing that the overall effect size (95 % CI) for pain relief was 0.51 (0.46 to 0.55) for placebo, and 0.03 (−0.13 to 0.18) for untreated controls [65].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Of the studies in our survey, four studies were performed without running a placebo group [12,14,16,17] and five trials did not include an active comparator [15,[18][19][20][21], clearly limiting the informative value of the studies. The particular importance of control groups for trials on OA has been underscored by a systematic review and meta-analysis involving 193 placebo (16,364 patients) and 14 untreated control groups (1167 patients) from RCTs, showing that the overall effect size (95 % CI) for pain relief was 0.51 (0.46 to 0.55) for placebo, and 0.03 (−0.13 to 0.18) for untreated controls [65].…”
Section: Discussionmentioning
confidence: 98%
“…Ninety percent of the patients randomized to active treatment with chicory and 50 % of the patients randomized to placebo showed 20 % improvement in pain, stiffness, and global assessment. Olsen et al concluded that the investigated proprietary chicory root extract was beneficial for the management of OA and deserves further investigation [19].…”
Section: Chicory Root Extractmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 In a study, the chicory extract's anti-inflammation features were evaluated and the important role of chicory in osteoarthritis was clarified. 12 The antibacterial features of this plant were also realized in different studies. [13][14][15][16] The antibacterial and antioxidation activities of the chicory plant have been proven before, but limited studies were performed on the antifungal features of this plant.…”
Section: 9mentioning
confidence: 99%